Analysis Of Tofu Sales Forecasting Using The Single Exponential Smoothing Method At UD. Tahu Murni, Gunungsitoli City - Nasrul Efendi Lase; Idarni Harefa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The development of the business world, especially in the food sector, is increasingly competitive, encouraging companies to improve the quality and quantity of sales. UD. Tahu Murni, which operates in Gunungsitoli City, faces the challenge of fluctuating market demand that can result in overstock and stockout. This study aims to analyze tofu sales forecasting using the Single Exponential Smoothing (SES) method. This method was chosen because of its ability to provide accurate estimates on data without clear trends. This study uses a quantitative approach with descriptive analysis of historical sales data. The forecasting results show that an alpha (α) value of 0.9 produces a sales estimate of 238,014 pieces with the lowest error (MAPE 0.83%). This finding indicates that SES is effective in predicting sales and supporting inventory management at UD. Tahu Murni. The proposed recommendations include the use of the SES method routinely, periodic monitoring, and training for human resources. With these steps, UD. Tahu Murni can improve operational efficiency and competitiveness in the soy-based food market.